ORGANIZATION AND FORMS OF INDEPENDENT WORK IN THE RUSSIAN LANGUAGE IN A SECONDARY SPECIAL EDUCATIONAL INSTITUTION - Kasymova F. S. (Web of Journals Publishing, 2024)
The article discusses the organization of independent work as a way of active, purposeful acquisition of new knowledge and skills by a student in the process of frontal, group and individual educational activities, carried out under the guidance of a teacher, but without the direct participation of a teacher.
Keywords: independent work, implementation of programs, information search, assimilation, application, knowledge transfer, fixation of results.